The Evaluation of Implementation Merdeka Curriculum at The Centre of Excellence Vocational High School - Abdul Muin Sibuea; Muhammad Amin; Bima Mustaqim; Ginagor Tumanggor (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to evaluate the implementation of the Merdeka Curriculum at the Centre of Excellence vocational high schools in North Sumatra. This study used a qualitative approach with CIPP (context, input, process, and product) evaluation model. The subjects used were school principals and teachers from vocational high school in North Sumatra by purposive sampling. Data collection techniques were carried out using questionnaires sent online via Google form and data analysis techniques using descriptive analysis. The research results showed that the implementation of the Merdeka Curriculum in vocational high schools, which have become centers of excellence, had been running quite effectively and efficiently even though, in terms of implementation, it still needs to be improved. Based on the research results, data was obtained in the context evaluation of the implementation of the Merdeka Curriculum at the Center of Excellence Vocational School; it was in the very good category. Likewise, the input evaluation was in the good category. Furthermore, the process evaluation was in the very good category, and the product evaluation was in the good category. The conclusion from this study is that teachers must be role models for students and can inspire students to develop their creativity. In addition, teachers need to upgrade their competence so that they can continue to learn to implement differentiation learning that is fun and pro-student.